Opportunities and Challenges of Islamic Bank Mergers in Indonesia During a Pandemic - Eka Setiana Susanti (ITB AAS INDONESIA Surakarta, 2021)
The presence of COVID-19 in Indonesia has had an impact on the economy, including the banking industry. However, the Shariah banking industry has not shown a positive trend. However, despite the positive trend in Shariah banking business, the penetration rate of the Indonesian Islamic banking market is still relatively small compared with traditional banking business. This led the government to decide to formulate a merger policy for the state-owned Sharia Bank, hoping that it can increase Indonesia’s market penetration. Considering the important role of Shariah banking industry in improving the national economy, this article aims to analyze the opportunities and challenges of Shariah banking merger policy. On the other hand, this policy was implemented during the COVID-19 pandemic. This article uses qualitative data analysis through descriptive methods and literature research methods. The data analysis focuses on the opportunities and challenges of the Indonesian government's Shariah Bank merger policy. Researchers use secondary data as a source for writing articles. According to the research results, the Indonesian Islamic Bank (BSI) formed after the merger provides many opportunities, such as increasing assets, expanding market penetration, and operating cost efficiency. At the same time, financing and operational risks are two major challenges that need to be paid attention to. This research helps stakeholders make decisions in the development of Islamic banking and finance.